2012
DOI: 10.2478/10004-1254-63-2012-2201
|View full text |Cite
|
Sign up to set email alerts
|

The Margin of Exposure to Formaldehyde in Alcoholic Beverages

Abstract: Formaldehyde has been classifi ed as carcinogenic to humans (WHO IARC group 1). It causes leukaemia and nasopharyngeal cancer, and was described to regularly occur in alcoholic beverages. However, its risk associated with consumption of alcohol has not been systematically studied, so this study will provide the fi rst risk assessment of formaldehyde for consumers of alcoholic beverages. Human dietary intake of formaldehyde via alcoholic beverages in the European Union was estimated based on WHO alcohol consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Formaldehyde is a natural ingredient of a variety of fruits, vegetables, meat, milk products and fish. Relatively high concentrations of formaldehyde were found in alcoholic beverages (Monakhova et al 2012). In an earlier survey of about 500 products of wine, beer, spirits and unrecorded alcohol, it was shown that only 1.8 % of the samples had formaldehyde levels above the WHO IPCS tolerable concentration.…”
Section: Formaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde is a natural ingredient of a variety of fruits, vegetables, meat, milk products and fish. Relatively high concentrations of formaldehyde were found in alcoholic beverages (Monakhova et al 2012). In an earlier survey of about 500 products of wine, beer, spirits and unrecorded alcohol, it was shown that only 1.8 % of the samples had formaldehyde levels above the WHO IPCS tolerable concentration.…”
Section: Formaldehydementioning
confidence: 99%
“…A 60-kg person would need to consume 0.8 L of alcohol at 14.37 mg/L daily to exceed the US EPA RfD of 0.2 mg/kg bodyweight/day, which is extremely unlikely even in this worst-case scenario (Jendral et al 2011). Monakhova et al (2012) estimated the human dietary intake of formaldehyde via alcoholic beverages in the European Union based on WHO alcohol consumption data and the literature on formaldehyde contents of beer, wine, spirits and unrecorded alcohol. The estimated human exposure to formaldehyde from alcoholic beverages averages 8 × 10 −5 mg/kg bodyweight/day, which was suggested as being below the threshold for public health concern (Monakhova et al 2012).…”
Section: Formaldehydementioning
confidence: 99%
“…Formaldehyde (methanal, CH 2 O, CAS # 50‐00‐0) is a colourless substance, which may be present in foods, beverages, industry and in the environment . The hazard of formaldehyde has been confirmed by the WHO International Agency for Research on Cancer (IARC), which found sufficient evidence for the carcinogenicity of formaldehyde .…”
Section: Introductionmentioning
confidence: 99%
“…The safety of these products has become an issue because many of them contain formaldehyde as an active ingredient, which is used for covalently altering keratins during the treatments to prolong the straightening effect [1,2]. Formaldehyde (methanal, CH 2 O, CAS # 50-00-0) is a colourless substance, which may be present in foods, beverages, industry and in the environment [3][4][5][6]. The hazard of formaldehyde has been confirmed by the WHO International Agency for Research on Cancer (IARC), which found sufficient evidence for the carcinogenicity of formaldehyde [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, formaldehyde exerts toxic effects on humans, including irritation of the eyes and respiratory tract, headaches, nausea, drowsiness and allergic skin reactions [14]. It is also considered a carcinogen by the International Agency for Research on Cancer (IARC) [15,16]. As it reduces the bacteria count and increases the shelf life of milk [17,18], several cases of milk adulteration by formaldehyde were recently reported [19].…”
Section: Introductionmentioning
confidence: 99%